Vibrio vulnificus Hemolysin: Biological Activity, Regulation of vvhA Expression, and Role in Pathogenesis - Yuan, Yuan (Front Immunol, 2020)
The Vibrio vulnificus (V. vulnificus) hemolysin (VVH) is a pore-forming cholesterol-dependent cytolysin (CDC). Although there has been some debate surrounding the in vivo virulence effects of the VVH, it is becoming increasingly clear that it drives different cellular outcomes and is involved in the pathogenesis of V. vulnificus. This minireview outlines recent advances in our understanding of the regulation of vvhA gene expression, the biological activity of the VVH and its role in pathogenesis. An in-depth examination of the role of the VVH in V. vulnificus pathogenesis will help reveal the potential targets for therapeutic and preventive interventions to treat fatal V. vulnificus septicemia in humans. Future directions in VVH research will also be discussed.